KAJIAN LITERATUR: EFEKTIVITAS LEARNING MANAGEMENT SYSTEM (LMS) DALAM MENINGKATKAN KEMANDIRIAN DAN HASIL BELAJAR SISWA DI ERA DIGITAL - Haikal, Ahmad; Azahra, Najwa; Awalia, Ananda Ayu (Paedagogie, 2025)
This study aims to analyze the effectiveness of the Learning Management System (LMS) in enhancing students’ independence and learning outcomes in the digital era by employing a literature-based Classroom Action Research (CAR) approach. The applied CAR model emphasizes a reflective cycle consisting of planning, implementation, observation, and evaluation stages in the use of LMS as a learning tool. This approach was chosen because it allows for a systematic examination of the learning process through the synthesis of findings from previous studies. The results indicate that the consistent implementation of LMS effectively fosters students’ autonomy in managing their learning activities, increases intrinsic motivation, and improves academic performance through structured and interactive learning experiences. Furthermore, the study reveals that the effectiveness of LMS implementation is significantly influenced by teachers’ digital competence, the relevance of instructional design, and adequate institutional support. Therefore, LMS has the potential to serve as a strategic instrument in promoting adaptive, independent, and sustainable learning across various levels of education.